Social Causes аnd Tendencies оf Drug Spreading Among Youth (оn тhe Case оf тhe Republic оf North Ossetia – Alania, Russian Federation) - Fedosova, Ekaterina (Journal of Sociology: Bulletin of Yerevan University, 2021)
Over the past years, the drug addiction of the population of Russia and especially young people is one of the most serious social problems, the scale of which made it a threat to national security. In order to develop effective ways and methods of counteracting drug addiction and crime, it is necessary to know the characteristics of all economic, social, criminal, and other factors influencing the drug situation. In the article, the author analyzes the results of the annual monitoring of the consumption and distribution of various types of drugs in the region of the Republic of North Ossetia - Alania, identifying the main social groups of drug addictions as well as social causes which stimulate drug addiction among youth.
Keywords: drug situation; prevention; youth problems; drug addiction; social causes